Examining the Advantages and Disadvantages of Nuclear Energy - Mohmandi, Zaman; Najibi, Najibullah (Journal of Natural Sciences – Kabul University, 2025)
Nuclear energy is one of the modern and powerful sources of energy, capable of providing continuous and stable electricity supply. This type of energy is produced through nuclear fission and fusion processes in nuclear reactors. This review-comparative study examines the advantages and disadvantages of nuclear energy and explores strategies to improve its utilization and address the challenges associated with this technology. Such strategies include enhancing safety measures, managing nuclear waste, diversifying energy sources, increasing transparency, and raising public awareness to mitigate the challenges of nuclear energy use. The results indicate numerous benefits, including high energy output from small amounts of fuel, zero greenhouse gas emissions, sustainability, continuous energy supply, and reduced dependence on fossil fuels. However, nuclear energy also presents several drawbacks, the most significant of which are safety risks, radioactive waste, high costs, and security concerns.